Reporting of patient-reported outcomes in trials on alcohol use disorder: a meta-epidemiological study. Issue 1 (25th April 2022) - Douglas, Alexander; Garrett, Elizabeth; Staggs, Jordan; Williams, Cole; Shepard, Samuel; Wise, Audrey; Hillman, Cody; Ottwell, Ryan; Hartwell, Micah; Vassar, Matt
Abstract : Objectives: Currently, limited research exists to assess the extent of patient-reported outcome (PRO) reporting among randomised controlled trials (RCTs) evaluating alcohol use disorder (AUD). We sought to investigate the completeness of reporting of PROs using the Consolidated Standards of Reporting Trials-PRO (CONSORT-PRO) extension in AUD RCTs. Design setting: Meta-epidemiological study. Methods: We searched MEDLINE, Embase and the Cochrane Central Register of Controlled Trials (CENTRAL) on 29 June 2021 for published RCTs focused on AUD. Following these searches, title and abstract screening, and full-text screening were performed by two investigators. To be included, a study must have employed a randomised trial design, published in English, focused on treatment of AUD and included at least one PRO. Trials meeting inclusion criteria were evaluated for completeness of reporting using the CONSORT-PRO extension adaptation. These trials were also evaluated for risk of bias (RoB) using the Cochrane RoB V.2.0 tool. Additionally, an exploratory analysis of each RCT's therapeutic area was extracted using the Mapi Research Trust's ePROVIDE platform. Screening and data collection were all performed in masked, duplicate fashion. Main outcome measures: PRO completeness of reporting, identification of factors associated with completeness of reporting and PRO measures used in RCTs to evaluate patients with AUD. Results: Nineteen RCTs were evaluated in our analysis. Our primary outcome, the mean completion score for CONSORT-PRO, was 40.8%. Our secondary outcome—the identification of factors associated with completeness of reporting—found that trials published after 2014 (ie, 1 year after the publication of the CONSORT-PRO extension) were 15.0% more complete than trials published before 2014. We found no additional associations with better reporting. Conclusions: We found that the completeness of PRO reporting in RCTs involving AUD was deficient. Complete reporting of PROs is instrumental in understanding the effects of interventions, encourages patient participation in their treatment and may increase clinician confidence in the value of PROs. High quality treatment strategies for AUD require properly reported PROs.